GLOBAL MIGRATION PATTERNS AND THE PRESERVATION OF CROATIAN NATIONAL IDENTITY IN EMIGRATION – THE EXAMPLE OF THE CROATIAN EMIGRANT COMMUNITY IN ROME - Komušanac, Monika (PUPIL: International Journal of Teaching, Education and Learning, 2024)
According to estimates, the expatriate community of Croats in Italy numbers between 15 and 20 thousand persons with Croatian citizenship, and in the province of Molise, where Croats have minority status, about 2 thousand. Considering the geographical proximity and the dynamics of Croatian-Italian external migration, it was determined that there is a lack of research that would explain the links between globalization and the preservation of national identity. Based on the conducted field research using survey methods and semi-structured interviews, the attitudes of teachers of Croatian remedial classes in Rome and students attending classes were examined, primarily on the challenges of the sustainability of Croats in terms of demographic, cultural and identity. The special feature of this Croatian emigrant community is that Croats in Rome do not have any specially recognized status, which is why their activities are partly limited. The emphasis of the research is on the study of the components of national identity, i.e. the language, culture, history and traditions of Croatia, which are taken care of by the Croatian supplementary education in Rome. Research will be conducted on the level of knowledge of the Croatian language, history and culture among the children of Croatian emigrants in Rome, the challenges of organizing Croatian classes in Rome, and the interest of Croatian emigrants in nurturing and maintaining ties with their homeland. The obtained results will be the basis for the revision of the existing system of organization of Croatian teaching abroad and for a better understanding of contemporary migration patterns and the phenomenon of Croatian emigration.